Meningkatkan Hasil Belajar Siswa Melalui Penerapan Multimedia Pembelajaran Praktik Belahan Tutup Tarik di Kelas X SMK Negeri 8 Surabaya - Veronica Purba; Marniati Marniati; Mein Kharnolis; Lutfi Hidayati (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2024)
The objectives of this study are (1) to find out the improvement of student learning outcomes through the application of multimedia, (2) to find out the response of students to the application of multimedia learning This research is a classroom action research. which will be carried out at SMKN 8 Surabaya in 2023/2024. The subject of this action is 33 students of class X Fashion Design 2. The data collection technique uses tests and questionnaires. The research instrument used cognitive test sheets and product assessments as well as questionnaire sheets. The data analysis technique used is quantitative descriptive. The results of the study show that: (1) Student learning outcomes through the application of multimedia practice of the pull-out closure have increased by 33%, increasing from the first cycle of 61% to 94% in the second cycle; (2) The students' response to multimedia learning received a percentage result of 81% which was categorized as very good.